Tingkat Partisipasi Kelompok Tani Hutan Karava Jaya dan Kelompok Tani Hutan Sumber Hidup Di Kecamatan Gumbasa - Sirenden, Diana; Golar, Golar; Maiwa, Arman; Hulu, Amati Eltriman (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
The Forest Farmers Group (KTH) is an organizational entity that specifically focuses on managing forest resources through the active participation of members in planning, implementation and evaluation activities. In achieving the goals of KTH activities, participation from KTH members is required. This research aims to determine the level of participation of KTH members in KTH activities starting from the planning stage, implementation stage, utilization stage and evaluation stage. Respondents are members of two KTHs, namely KTH Jaya Karava and Sumber Hidup. Data collection was carried out through interviews and direct observation in the field. Data analysis used in this research uses quantitative descriptive analysis. The results of the research show that the level of participation of members of the KTH Jaya Karava group is relatively high, while the level of participation of KTH Sumber Hidup is relatively low.